2020
DOI: 10.3389/fonc.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Intravesical Chemotherapy Reduce Recurrence Rate for Non-muscle Invasive Bladder Cancer Patients: A Meta-Analysis

Abstract: Background: Non-muscle invasive bladder cancer accounts for nearly 80% of newly diagnosed bladder cancer cases, which often recur and progress. This meta-analysis was evaluated by the adverse events and recurrence rate of thermal intravesical chemotherapy vs. normal temperature intravesical chemotherapy in the treatment of non-muscle invasive bladder cancer. Methods: A systematic review and cumulative analysis of studies reporting adverse events and recurrence rate of thermal intravesical chemotherapy vs. norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…e effects of postoperative bladder intravesical chemotherapy: reducees recurrence rate, delays recurrence time, prevents infiltration and metastasis, improves survival rate, prolongs survival time, and improves quality of life [12]. Studies have shown that bladder intravesical chemotherapy can significantly reduce the recurrence rate of non-muscleinvasive bladder cancer after surgery [13][14][15]. e size of the drug dose, the frequency of treatment, and the length of the treatment course all have relative effects on the clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“…e effects of postoperative bladder intravesical chemotherapy: reducees recurrence rate, delays recurrence time, prevents infiltration and metastasis, improves survival rate, prolongs survival time, and improves quality of life [12]. Studies have shown that bladder intravesical chemotherapy can significantly reduce the recurrence rate of non-muscleinvasive bladder cancer after surgery [13][14][15]. e size of the drug dose, the frequency of treatment, and the length of the treatment course all have relative effects on the clinical effect.…”
Section: Discussionmentioning
confidence: 99%
“… 121 , 123 , 124 It involves the intravesical application of heated chemotherapy to the bladder through use of microwaves to heat the local bladder environment or through circulation of heated fluids (hyperthermic intravesical chemotherapy [HIVEC]). 121 , 122 , 125 , 126 In a meta-analysis of 12 studies, intravesical chemothermotherapy was associated with a significantly decreased risk of disease recurrence compared with normal-temperature chemotherapy after 2 years, with no difference in the rate of AEs. 125 However, AEs of hematuria, bladder spasms, and pain have been reported with chemothermotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 121 , 122 , 125 , 126 In a meta-analysis of 12 studies, intravesical chemothermotherapy was associated with a significantly decreased risk of disease recurrence compared with normal-temperature chemotherapy after 2 years, with no difference in the rate of AEs. 125 However, AEs of hematuria, bladder spasms, and pain have been reported with chemothermotherapy. 122 , 127 While no studies on chemothermotherapy were identified in our SLR, it is a treatment option that should be considered by the treating physician.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal temperature chemotherapy, there was a significantly lower recurrence rate with the use of thermal chemotherapy at 2-year follow-up (RR= 0.3, 95% CI: 0.21-0.43). Adverse events did not significantly differ between the two groups, making this a viable option [54,55]. The analysis, however, was limited by the heterogeneity of chemotherapeutic agents and protocols utilized as well as varied risk levels amongst the study participants, which may bias direct comparisons.…”
Section: Novel Modes Of Drug Deliverymentioning
confidence: 99%